Efforts to Increase Public Awareness of Sharia Insurance Products in Indonesia Through Management Functions - Irawan Agung Wibowo; Ibrahim Kholilul Rohman (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
Islamic insurance, known as Sharia Insurance, has become a crucial component in Indonesia's financial sector. Sharia insurance prioritizes Islamic economic principles by offering products such as takaful (collective insurance) and mudharabah (business partnership). The opportunities for the Sharia insurance industry in Indonesia are substantial, given that the Muslim population comprises 87.2% of the total population as of 2021. Additionally, the Financial Services Authority Regulation (FSAR) Number 11 of 2023, Article 15, mandates Sharia financial institutions to prioritize Sharia financial products. However, data indicates that the growth of Sharia insurance is still significantly low. As of December 31, 2022, the market share of Sharia insurance premiums is only 4.76%. In light of the above challenges and opportunities, this study aims to analyze the constraints, particularly the issue of product awareness, where many individuals still do not fully comprehend and appreciate the benefits of Sharia insurance products. Therefore, this article discusses 1) the factors influencing the lack of understanding and awareness among the public regarding the benefits of Sharia insurance products, and 2) the efforts to address this issue. This research adopts a qualitative approach, utilizing a systematic literature review method for data analysis. Books and other literature relevant to the predetermined theme were systematically searched to provide insights into the challenges and potential solutions for enhancing awareness and understanding of Islamic Insuranceproducts among the public.